2006
DOI: 10.1143/jjap.45.l444
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Fine and Coarse Ripples on 4H–SiC Single Crystal Induced by Femtosecond Laser Irradiation

Abstract: Upon femtosecond pulsed-laser irradiation, periodic structures referred to as “ripples” were fabricated on the surface of a 4H–SiC single crystal. The periodic structures consisted of two concentric regions in the irradiated spots which were clearly distinguished by the period. Surface morphologies were characterized as a function of energy, accumulation number, and interval of pulses. The difference in the threshold of fine and coarse ripples was identified for the first time. The possible formation mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…1,2 In the recent experimental studies using femtosecond lasers, however, several groups have observed a new type of periodic structures with much smaller periods than the wavelength. [3][4][5][6][7][8][9][10] In most cases, these subwavelength structures or nanostructures are produced at relatively low fluences of laser pulses. In fact, superimposed femtosecond laser pulses at fluences less than the single-pulse ablation threshold have produced the nanostructure with the period as small as ϳ /10 or ϳ30 nm on hard thin films such as TiN and diamondlike carbon ͑DLC͒.…”
Section: Ultrafast Dynamics Of Periodic Nanostructure Formation On DImentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 In the recent experimental studies using femtosecond lasers, however, several groups have observed a new type of periodic structures with much smaller periods than the wavelength. [3][4][5][6][7][8][9][10] In most cases, these subwavelength structures or nanostructures are produced at relatively low fluences of laser pulses. In fact, superimposed femtosecond laser pulses at fluences less than the single-pulse ablation threshold have produced the nanostructure with the period as small as ϳ /10 or ϳ30 nm on hard thin films such as TiN and diamondlike carbon ͑DLC͒.…”
Section: Ultrafast Dynamics Of Periodic Nanostructure Formation On DImentioning
confidence: 99%
“…It is well known, however, that the nanostructure formation with femtosecond laser pulses cannot be explained by the conventional ripple model, and thus the physical mechanism creating such nanostructures is an important subject to study. [5][6][7][8][9][10][11][12][13] In the previous experiments for DLC films, Yasumaru et al 12 and Miyazaki et al 13 have found that the nanostructure formation on the DLC surface is accompanied by the bonding structure change from DLC to glassy carbon ͑GC͒, and that the reflectivity change on the DLC surface is a good measure to monitor the experimental conditions to induce these morphological and bonding structure changes. These experiments suggested that the change in bonding structure may be a key to understanding the detailed process responsible for the nanostructure formation.…”
Section: Ultrafast Dynamics Of Periodic Nanostructure Formation On DImentioning
confidence: 99%
“…For example, our group and collaborators observed the structure size as small as ~ λ/10 or 30 nm on hard thin films such as titanium nitride (TiN) and diamond-like carbon (DLC) films with superimposed fs pulses at fluence less than the single-pulse ablation threshold [3]. Similar fine periodic structures produced with fs laser pulses have been reported for various kinds of materials such as BaF 2 , CaF 2 [2], diamond [4], TiN [1,3], AlN [7], CrN [9], GaN [11], SiC [6,7,13], Si [8], GaP, GaAs [5], InP [5,10], and ZnSe [12], where the ablation traces are usually oriented to the direction perpendicular to the laser polarization.…”
Section: Introductionmentioning
confidence: 57%
“…When intense femtosecond (fs) laser pulses are focused on solid surfaces, periodic fine structures are often observed that are much smaller than the laser wavelength λ used [1][2][3][4][5][6][7][8][9][10][11][12][13], being in contrast to the so-called ripples with the structure period close to λ [14]. Such nanostructures have usually been produced at low fluence around the ablation threshold of each material.…”
Section: Introductionmentioning
confidence: 99%
“…Much attention is focused on the laser treatment of materials and the physicochemical and other processes accompanying it [7][8][9][10][11][12][13]. Laser treatment in air of SiC ceramics is accompanied by both surface oxidation and the occurrence of oxidation products in the gaseous phase [3,8,14].…”
Section: Introductionmentioning
confidence: 99%